2023
DOI: 10.7759/cureus.35404
|View full text |Cite
|
Sign up to set email alerts
|

An Equity Analysis of Zero-Dose Children in India Using the National Family Health Survey Data: Status, Challenges, and Next Steps

Abstract: Background While immunization programs across the world have made considerable progress, children and communities continue to be beyond the reach of healthcare services. Globally, they are now referred to as zero-dose (ZD) children (those who have not received a single dose of diphtheria, pertussis, and tetanus-containing vaccine). Pre-COVID-19 pandemic analyses suggest that nearly 50% of vaccine-preventable deaths occur among ZD children. Two-thirds of these children live in extremely poor househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The research identified areas for further inquiry. Additional gender research is needed to include complex issues such as working parents, the link between health services and daycare, building on recent analysis in this space [ 32 , 33 ]. The interventions mapped in the analysis are only proposed interventions, and the efficacy and impact of the interventions remains a key research gap [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research identified areas for further inquiry. Additional gender research is needed to include complex issues such as working parents, the link between health services and daycare, building on recent analysis in this space [ 32 , 33 ]. The interventions mapped in the analysis are only proposed interventions, and the efficacy and impact of the interventions remains a key research gap [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were an estimated 12.4 million ZD children in 2020, the majority living in sub-Saharan Africa or other conflict-affected areas [ 1 , 2 ]. Pre-Covid-19 pandemic investigations indicated that nearly 50% of vaccine preventable deaths occurred among ZD children [ 3 ]. The World Health Organisation Immunization Agenda 2030 (IA2030) identified reaching out to ZD children as a strategic priority and has set a target of a 25% reduction in the number of ZD children by 2025 and 50% by 2030 [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%